2013
DOI: 10.1103/physrevc.87.041301
|View full text |Cite
|
Sign up to set email alerts
|

Slater approximation for Coulomb exchange effects in nuclear covariant density functional theory

Abstract: The relativistic local density approximation (LDA) for the Coulomb exchange functional in nuclear systems is presented. This approximation is composed of the well-known Slater approximation in the nonrelativistic scheme and the corrections due to the relativistic effects. Its validity in finite nuclei is examined by comparing with the exact treatment of the Coulomb exchange term in the relativistic Hartree-Fock-Bogoliubov theory. The relativistic effects are found to be important and the exact Coulomb exchange… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…In the following, we will further verify the present approach by comparing with the fine structure of SD excitations in 16 O, in which the strength distributions from each individual spin-parity component (J π = 0 − , 1 − , and 2 − ) have been identified by using the 16 O( p, n) 16 F reaction with a polarized proton beam [13]. Such detailed experimental data provide a rigorous calibration for the theory.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the following, we will further verify the present approach by comparing with the fine structure of SD excitations in 16 O, in which the strength distributions from each individual spin-parity component (J π = 0 − , 1 − , and 2 − ) have been identified by using the 16 O( p, n) 16 F reaction with a polarized proton beam [13]. Such detailed experimental data provide a rigorous calibration for the theory.…”
Section: Introductionmentioning
confidence: 83%
“…To follow this direction, the investigation on the relativistic local density approximation (LDA) for the Coulomb Fock terms has also been preformed [16]. This approximation is composed of the well-known Slater approximation in the non-relativistic scheme and the corrections due to the relativistic effects.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear self interactions in Lagrangian density can be expressed in the following form [22,40,44]…”
Section: A Model Descriptionmentioning
confidence: 99%
“…It is worthy also here to note that in Skyrme Hartree Fock (SHF) models, the Coulomb exchange contribution is retained by many of SHF parametrization. Recently, the relativistic local density approximation (LDA) for the Coulomb exchange functional in nuclear systems was investigated [40]. They have found that the important relativistic effects and the exact Coulomb exchange energies can be reproduced by the relativistic LDA within 5 % demonstrated for semi magic Ca, Ni, Zr, Sn, and Pb isotopes from proton dripline to neutron dripline.…”
Section: Introductionmentioning
confidence: 99%